The effect of employees’ personal values on work-life balance and well-being – An empirical study in Vietnam - Mai Thi My , Quyen; Ta Thi , Thanh; Le Nguyen, Hau (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
Well-being is nowadays an important issue for employees and firms striving for sustainable development. This issue is complicated because individual employees subjectively and differently perceive their personal values and the relative importance of their work, life, and well-being. This study thus explores the effects of different types of personal value on work-life balance and subjective well-being. Based on the data surveyed from 246 employees in Vietnam, the results show that value for self-enhancement positively affects work-life conflict, leading to decreased well-being. In contrast, value for conservation alleviates work-life conflict and facilitates work-life enhancement, both of which improve the well-being of employees. These two types of personal values have been found being co-existed in individuals at different levels, therefore, it is possible for firms to promote both values for conservation and value for self-enhancement.